2010
DOI: 10.1055/s-0030-1249658
|View full text |Cite
|
Sign up to set email alerts
|

Hormone and Sperm Analyses after Chemo- and Radiotherapy in Childhood and Adolescence

Abstract: Paediatric oncological therapy seems to have led to fertility impairment in about 1/3 of the participants. Considering this serious impairment, patients and their families should be given comprehensive counselling ahead of therapy to enable fertility-preserving measures. For persons who wish to have children after undergoing therapy we recommend a hormone and sperm analysis. An early analysis may enable a more successful family planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
35
1
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 17 publications
(18 reference statements)
2
35
1
3
Order By: Relevance
“…In the few studies of childhood cancer survivors [8,9,20] AMH values are markedly lower compared with aged-matched normative data [6,24]. The AMH levels in our CLSs decreased along treatment gonadotoxicity, and almost all survivors after ''high-toxic'' treatment had critically low values.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…In the few studies of childhood cancer survivors [8,9,20] AMH values are markedly lower compared with aged-matched normative data [6,24]. The AMH levels in our CLSs decreased along treatment gonadotoxicity, and almost all survivors after ''high-toxic'' treatment had critically low values.…”
Section: Discussioncontrasting
confidence: 54%
“…Eleven % of our male CLSs were considered to be infertile. In other studies among survivors treated for several types of childhood cancer, azospermia was found in about 30% of the survivors, and elevated FSH levels were observed in approximately every third survivor [20,21]. Elevated FSH is generally viewed to reflect reduced spermatogenesis, and may on a group level together with a single sperm count be useful to screen for possibility of future parenthood.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…3 Impaired fertility is a well-known side effect after HSCT in childhood and adolescence but studies in the field are often limited by small numbers of patients in the various groups. [21][22][23] A recent study on the recovery of spermatogenesis after HSCT reported that spermatozoa were found in sperm fluid analyses in 58 of 217 males (27%) after a median follow-up period of 4.5 years. 24 A recent review of paediatric HSCT reported that impaired fertility was present in nearly all females treated with conditioning protocols including BU.…”
Section: Discussionmentioning
confidence: 99%
“…In males, however, pre-pubertal therapy was found to increase the risk for infertility, which is inconsistent with findings of other recent studies. 21 The fact that TBI was a significant risk factor for infertility in males is not surprising given that impaired sperm production in the form of temporary oligospermia occurs after radiotherapy at dosages as low as 0.1 Gy. This azoospermia may resolve over a period of years.…”
Section: Discussionmentioning
confidence: 99%